Rancang Bangun Sistem Informasi Penjualan Mitra dan Pendapatan Secara Real-time Berbasis Web : Studi Kasus Es Teh Arjuna di Kota Tegal - Farchatul Hudayah; Slamet Wiyono; Zaenul Arif (Jurnal Penelitian Teknologi Informasi dan Sains, 2026)
Advancements in information technology encourage MSMEs to utilize information systems to enhance the effectiveness of their business management. Es Teh Arjuna, an MSME in Tegal City, faces challenges in monitoring partner sales and managing revenue because transactions are recorded manually using disparate methods; this results in slow data recapitulation, a risk of recording errors, and difficulty for the business owner in quickly accessing sales information. This study aims to analyze requirements, design, develop, and test a web-based information system for partner sales and revenue that provides information in  real-time. The Waterfall model was used for system development, while data collection involved observation, interviews, and a literature review. The system was developed using PHP and MySQL and tested via Black Box Testing. The results demonstrate that the system successfully integrates sales data from all outlets into a centralized database, streamlining the management of products, outlets, employees, cashiers, and sales transactions, as well as facilitating the generation of revenue reports for specific periods. Furthermore, the system enables the business owner to monitor sales performance more quickly, accurately, and systematically, thereby supporting decision-making and improving the operational efficiency of Es Teh Arjuna.